1982
DOI: 10.1002/lipi.19820840207
|View full text |Cite
|
Sign up to set email alerts
|

Fettsäuren der Samenöle europäischer Wildpflanzen ‐ Ein Ansatzpunkt für die Entwicklung von industriellen Nutzpflanzen?

Abstract: Die Suche nach neuen Ressourcen für die Gewinnung von Industriegrundstoffen schließt die Pflanzenwelt mit ein. Unter den krautartigen Pflanzen stellen die samenölhaltigen Arten die wichtigste Gruppe potentieller Nutzpflanzen dar, die durch intensive züchterische Bearbeitung zu einer landwirtschaftlichen Ölfrucht entwickelt werden können. Obwohl seit Jahren in vielen Ländern, insbesondere in den USA, entsprechende Entwicklungsprogramme laufen, ist in Europa eine Evaluierung der heimischen Wildflora, und insbeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Some wild plant seeds have been reported with high content of long-and very-long-chain saturated fatty acids, in which lignoceric acid is present in high percentages (Spitzer et al, 1990). Akhtar et al, (1986) reported that some seeds of the Cruciferae family, such as Erysimum perofskianum, have lignoceric acid in their oils up to 23.2%; Hondelmann and Radatz (1982) found that Lunaria annua oil has 21% of this FA; and Sultana and Gulzar (2012) found that this fatty acid is present in the Adenanthera pavonina oil at a level of 20.24%.…”
Section: Fatty Acid Composition Of Tsomentioning
confidence: 99%
“…Some wild plant seeds have been reported with high content of long-and very-long-chain saturated fatty acids, in which lignoceric acid is present in high percentages (Spitzer et al, 1990). Akhtar et al, (1986) reported that some seeds of the Cruciferae family, such as Erysimum perofskianum, have lignoceric acid in their oils up to 23.2%; Hondelmann and Radatz (1982) found that Lunaria annua oil has 21% of this FA; and Sultana and Gulzar (2012) found that this fatty acid is present in the Adenanthera pavonina oil at a level of 20.24%.…”
Section: Fatty Acid Composition Of Tsomentioning
confidence: 99%